Interactive sonification of flow pressure patterns due to hand-water-interaction of elite crawl stroke swimmers - Perception is more substantial when flow listening is added to flow sensing - Ungerechts, B. E.; Hamann, M.; Cesarini, D.; Hermann, T. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Swimming crawl stroke is more effective when the swimmer perceives well the local flow change due to alternating hand-water-interaction (HWI), representing local change of volumetric energy density (VED). In most cases it is unknown whether the flow is bilaterally symmetric and in case if not, how a swimmer can change HWI. It is assumed that interactive sonification (ISon) system of the local change VED together with perceived water flow can be a tool with which the swimmer can improve propulsive efficiency by matching the flow effects bilaterally. The local VED change was registered via flow probes and sonified data acted in real time via headphones as augmented feedback. The question was if swimmers could bring the effects of HWI to the same level through ISon use, without any prescriptions how to act. Ten elite crawl stroke swimmers, after split into control and interactive group, following the same test protocol in one week (C-group had not ISon intervention). Both groups participated in the same pre- and posttests, fully equipped but without audible feedback. In the posttest all swimmers swam faster and 60 % (I-group) showed remarkable peak flow pressure effects versus 16 % (C-group). However, similarity of hands effects was never reached. 80 % (I- group) switched the laterality versus 0 % (C-group). Swimmers named ISon system use an "eye-opener", which supports to perform HWI during each cycle mentally more controlled.